The prognostic value of right ventricular ejection fraction by cardiovascular magnetic resonance in heart failure: A systematic review and meta-analysis. (1st December 2022) - Papanastasiou, Christos A.; Bazmpani, Maria-Anna; Kokkinidis, Damianos G.; Zegkos, Thomas; Efthimiadis, Georgios; Tsapas, Apostolos; Karvounis, Haralambos; Ziakas, Antonios; Kalogeropoulos, Andreas P.; Kramer, Christopher M.; Karamitsos, Theodoros D.
Abstract: Background: Cardiac magnetic resonance (CMR) is considered the gold standard for the assessment of right ventricular ejection fraction (RVEF). Previous studies have suggested that RVEF may be a predictor of adverse outcomes in heart failure (HF). In this study, we aimed to systematically review the prognostic value of RVEF, evaluated by CMR, across the spectrum of left ventricular systolic function in patients with HF. Methods: Electronic databases were searched for studies investigating the prognostic value of RVEF in HF, irrespective of left ventricular ejection fraction (LVEF). A random-effects meta-analysis was conducted for mortality and HF hospitalization. Subgroup analyses were also performed based on the presence of reduced (<50%) or preserved LVEF (≥50%). Results: In total, 46 studies enrolling 14, 344 patients were included. In the pooled analyses, impaired RVEF was a powerful predictor of mortality (HR: 1.26, 95% CI: 1.18–1.33, I 2 : 13%, per 10% decrease in RVEF) and death or HF hospitalization (HR: 1.31, 95% Cl: 1.2–1.42, I 2 : 27%, per 10% decrease in RVEF). A decrease in RVEF was strongly associated with increased risk of mortality or hospitalization both in HF with reduced EF (HR: 1.24, 95% CI: 1.13–1.36, I 2 : 2%, per 10% decrease in RVEF) and in HF with preserved EF (HR: 1.24, 95% CI: 1.09–1.40, I 2 : 0%, per 10% decrease in RVEF). Conclusion: Impaired RVEF on CMR strongly predicts adverse outcomes in patients with HF regardless of LVEF. RV systolic function should be carefully evaluated in these patients. Prospero Registration: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021256967 Highlights: Impaired RVEF on CMR strongly predicts adverse outcomes (i.e. death, HF hospitalization) in patients with HF, regardless of LVEF Impaired RVEF on CMR is a strong predictor of mortality in both ischemic and non-ischemic cardiomyopathy RV systolic function should be carefully evaluated and thoroughly reported in patients with HF, especially during a CMR exam.